2019
DOI: 10.31788/rjc.2019.1215019
|View full text |Cite
|
Sign up to set email alerts
|

BIOLOGICAL ACTIVITY OF METHANOL EXTRACT OF Elaeocarpus mastersii KING: ANTIOXIDANT, ANTIBACTERIAL, AND α-GLUCOSIDASE INHIBITOR

Abstract: Plants are one of the natural resources that have great biological activity and have long been used in traditional medicine. In this research, methanol extracts of root, stem bark, and leaf of Elaeocarpus mastersii King were tested to determine phenolic and flavonoid content and evaluate their biological activities as the antioxidant, antibacterial, and antidiabetic using the method of DPPH (2,2-diphenyl-1-picrylhydrazyl) assay, disc diffusion against Staphylococcus epidermidis (S. epidermidis), Staphylococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Therefore, inhibition of α-glucosidase will be one of the most effective approaches to control diabetes (Sheikh et al, 2008). Elaeocarpus genus is used as folk medicines for diabetics and hypertensive disease (Okselni et al, 2019). Talukdar et al (2016) state that in vitro anti-diabetic activity of E. ganitrus bark extract has an inhibitory effect on the α-amylase enzyme which may be used to control high blood glucose levels.…”
Section: In Vitro Anti-diabetic Activitymentioning
confidence: 99%
“…Therefore, inhibition of α-glucosidase will be one of the most effective approaches to control diabetes (Sheikh et al, 2008). Elaeocarpus genus is used as folk medicines for diabetics and hypertensive disease (Okselni et al, 2019). Talukdar et al (2016) state that in vitro anti-diabetic activity of E. ganitrus bark extract has an inhibitory effect on the α-amylase enzyme which may be used to control high blood glucose levels.…”
Section: In Vitro Anti-diabetic Activitymentioning
confidence: 99%
“…Antibacterial activity was detected after incubation for 24 h at 30 o C. A clear zone of inhibition in the media was considered as an indicator of antibacterial activity. 11,12,13…”
Section: Antibacterial Activity Testingmentioning
confidence: 99%
“…Elaeocarpus mastersii King belongs to Elaeocarpus genus that spread widely in Indonesia. This plant has high total phenolic contents [16,17]. Unfortunately, the literature studies showed that the isolated compounds of E. mastersii King were limited to the compounds of anthocyanins, cucurbitacins, ellagic acid derivatives, β-sitosterol, and βsitosterol glucoside [18][19][20].…”
Section: Introductionmentioning
confidence: 99%